A flood susceptibility model at the national scale based on multicriteria analysis - Santos, Pedro Pinto (2021)
River flooding is a specific worldwide type of flooding responsible for considerable human and material losses. An extensive knowledge about flood conditioning factors and a diverse set of methodologies for flood susceptibility evaluations are available, although there is still field for improvement regarding methodologies for small-scale flood susceptibility assessment, particularly relevant in data-scarce contexts. This research applied to mainland Portugal, introduces a multicriteria methodology to assess flood susceptibility at national scale considering three flood-conditioning factors: flow accumulation, average slope angle and average relative permeability. These three factors resume other factors usually considered in literature, related to morphology and potential runoff. This work includes data from the flood conditioning factors considering the cumulative role of the entire contributive area and not only the on-site characteristics. The weight of each factor was assigned based on expert opinion and validated using available flood damages databases with >150 years of records. From the several tested flood susceptibility models, the one that best fits the historical records was chosen, which corresponds also to a more valued role of flow accumulation factor. Results provide an accurate differentiation of transboundary, regional and local rivers. The scores of stream flood susceptibility were later transformed to a single value per each of the 278 municipalities of mainland Portugal. Representing the natural susceptibility to river flooding, these results can be cross-analyzed with structural mitigation measures, spatial planning instruments, exposure and vulnerability data along the respective floodplains, in order to identify water streams that require a more detailed and concerned future intervention and an exhaustive susceptibility study at the local scale.